Para ler os sinais dos tempos: as estratégias da Igreja Católica no Brasil frente às subjetividades religiosas contemporâneas de seus fiéis. - Cruz, Claudia Maria da Silva (2020)
It is an observable phenomenon that Catholicism, globally, has suffered a bleeding in the number of its faithful every year. Data from the 2010 Census, for example, demonstrate an increasing trend in the levels of religious pluralism and diversity in Brazil, while the decrease, year by year, in the total of those who declare themselves Catholics is attested. In the specialized literature, there is also a discussion that points to an increase in the diversity of practices and discourses in the Brazilian Catholic field, starting from the study of the observed subjectivities. It is through the analysis of these phenomena that it is noticed, in some cases, the rupture of some precepts of the Church's conservatism, which leads to promote a new present reflection on the future of the Catholic Church in the country. It is proposed here to understand how the pastoral strategies of the leaders of the Catholic Church in Brazil face the problem of the new contemporary religious subjectivities of their faithful, which increasingly demonstrate the autonomy of the subjects in the configuration of their faith, in an environment of great diversity and at a time of growing religious plurality. This is done through documentary and bibliographic analysis of the documents produced by the Confederation of Bishops of Brazil, to guide Catholic parishes and communities in the different dioceses, which present themselves pastorally as a reaction to a scenario where these typical contemporary phenomena are punctuated. The study revealed that the role of the Church in this context is precisely to seek to understand identities that are excluded or marginalized, showing the positive side that are often hidden, or ignored by society. The opening of the Church to these new identities, allows to place more hope within the communities, creating spaces to work their cultural, social and religious conflicts, without losing respect for diversity, creating a healthy space of coexistence without losing the identity of each one. one. Therefore, the General Guidelines for the Evangelizing Action of the Church in Brazil are the way found to respond to the challenges of a country that, in the second decade of this 21st century, is undergoing major changes in all areas. In fact, there is a concern by the Catholic Church to show that missionaries who are not based on community life are at risk of becoming lonely walkers, without existential references for their work.